Exploring presence practices: a study of unit managers in a selected Provincial Hospital in Free State Province - Bernardine Smith; Precious Chibuike Chukwuere; Leepile Alfred Sehularo (BMC, 2024)
Abstract Background Nursing presence depends on an individual's belief system, truths, sensory experience, professional skills, and active listening. Thus, one may assume that presence occurs when nurses care for patients in a kind and compassionate way. This study aimed to explore and describe presence practices amongst unit managers in a selected provincial hospital in Free State Province. Methods A qualitative research approach with an exploratory descriptive contextual research design was employed in this study. A purposive nonprobability sampling technique was utilised to select participants. Data were collected through semi-structured interviews and analysed using the six steps of thematic qualitative data analysis. The study's trustworthiness was ensured through ascertaining credibility, dependability, confirmability, transferability, and authenticity. Approval to conduct the study was obtained from the North-West University Health Research Ethics Committee (NWU-HREC), DoH in the Free State Province, and the CEO (the gatekeeper) of the selected hospital. Results Four themes were generated, namely, presence practices amongst unit managers in a selected provincial hospital in Free State, the impact of presence practices on hospital dynamics in a selected provincial hospital in Free State, unit managers' practices of relational care and human connectedness in the unit, and the perceptions of unit managers on barriers to presence practices in a selected provincial hospital in Free State. Each of these themes presents categories and sub-categories. Unit managers actively foster supportive work cultures, effective management, human connectedness and relational care, and effective communication to yield team cohesion and positive impacts on patient care. Unit managers also display resilience and highlight the need for ongoing support from colleagues and top management. Conclusion Unit managers exhibit diverse presence practices which emphasise their commitment through visibility and accessibility despite staff shortages and resource constraints.